Career preferences of graduate and non-graduate entrants to medical schools in the UK. - Goldacre, M; Davidson, J; Lambert, T (2007)
OBJECTIVE: Recent UK policy has been to increase substantially the number of graduate entrants to medical schools. Our aim was to study whether graduate and non-graduate entrants have different long-term career preferences. METHODS: We conducted postal questionnaire surveys of medical qualifiers from all UK medical schools in 1999, 2000 and 2002, surveyed 1 year after qualification, and qualifiers of 1999 and 2000, surveyed 3 years after qualification. RESULTS: By Year 3 after qualification, general practice was the choice of 33% of men graduate entrants and 21% of men non-graduates ( = 12.5, P < 0.001) and of 43% of women graduates and 38% of women non-graduates ( = 1.6, P = 0.2). Surgery was a much less popular choice for men graduate entrants than for men non-graduates; but similar percentages of women graduate and non-graduate entrants chose surgery. A lower percentage of graduate entrants than of non-graduates favoured paediatrics. Other differences between graduates and non-graduates were generally small. General practice was the preferred career for a much lower percentage of those who took an intercalated degree while at medical school, than of those who did not. CONCLUSIONS: Increasing graduate entry to medical school is likely to increase the percentage of doctors who want to become general practitioners, but only modestly so. It may also lead to a decline in the percentages choosing surgery and paediatrics. Otherwise, at least on the current criteria used for selecting students, increasing graduate entry will probably not make much difference to the percentage of newly qualified doctors seeking careers in different branches of practice.